Eight weeks of dynamic stretching during warm-ups improves jump power but not repeated or single sprint performance - Turki-Belkhiria, L.; Chaouachi, A.; Turki, O.; Chtourou, M.; Chtara, M.; Chamari, K.; Amri, M.; Behm, D. G. (European Journal of Sport Science, 2014)
There is abundant research involving the acute effects of stretching on subsequent performance; however, there is little information on dynamic stretch training programmes on range of motion (ROM), power and speed measures. It was the objective of this research to examine the training consequences of active dynamic stretching (ADS) and static dynamic stretching (SDS). A repeated measures design compared the effects of 8 weeks of warm-ups incorporating two dynamic stretch modalities: ADS and SDS on squat jump (SJ), countermovement jump (CMJ), 20-m sprint performances and repeated sprint ability (RSA) and hip ROM in 37 male soccer players. SJ height (SDS: 4.6%; ADS: 5.3%; p <0.05), CMJ height (SDS: 5.3%; ADS: 3.4%; p<0.05), CMJ force (SDS: 7.2%; ADS: 12.7%; p<0.001) and CMJ peak power (SDS: 3.9%; ADS: 3.3%; p<0.05) increased significantly after SDS and ADS training compared to the control group (no significant change). Sprint performance and RSA were not affected by either of the dynamic stretch training regimens. The SDS and ADS training programmes elicited similar improvements in flexibility (SDS: 57.6%; ADS: 45.1%; p<0.01) compared to the non-significant changes in the control group. The inclusion of ADS and SDS within the regular warm-up of an 8-week training programme can improve not only flexibility but also jump power measures as well.